Mechanism and Therapeutic Opportunities of Histone Modifications in Chronic Liver Disease - Cai, Qiuyu; Gan, Can; Tang, Chengwei; Wu, Hao; Gao, Jinhang (Frontiers in Pharmacology, 2021)
Chronic liver disease (CLD) represents a global health problem, accounting for the heavy burden of disability and increased health care utilization. Epigenome alterations play an important role in the occurrence and progression of CLD. Histone modifications, which include acetylation, methylation, and phosphorylation, represent an essential part of epigenetic modifications that affect the transcriptional activity of genes. Different from genetic mutations, histone modifications are plastic and reversible. They can be modulated pharmacologically without changing the DNA sequence. Thus, there might be chances to establish interventional solutions by targeting histone modifications to reverse CLD. Here we summarized the roles of histone modifications in the context of alcoholic liver disease (ALD), metabolic associated fatty liver disease (MAFLD), viral hepatitis, autoimmune liver disease, drug-induced liver injury (DILI), and liver fibrosis or cirrhosis. The potential targets of histone modifications for translation into therapeutics were also investigated. In prospect, high efficacy and low toxicity drugs that are selectively targeting histone modifications are required to completely reverse CLD and prevent the development of liver cirrhosis and malignancy.